Maternal Cardiac Functional and Structural Changes in Preeclampsia: an Echocardiographic Study - Parveen, Nahid; Begum, Shahnaj; Nahid, Sanzida (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: Preeclampsia is a pregnancy-induced multi-organ syndrome of acute cardiovascular manifestations with significant short and long-term sequelae. However, there is a relative lack of knowledge with respect to cardiac functional and structural changes in women with preeclampsia Therapeutic interventions used in the management of preeclampsia may cause iatrogenic adverse consequences due to this lack of knowledge. The present study was therefore designed to evaluate the echocardiographic changes in cardiac structural and functional indices in pregnant women with PE. Methods: This cross-sectional study was carried out in the Department of Obstetrics and Gynaecology Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka Medical College Hospital (DMCH), and Shaheed Suhrawardy Medical College Hospital (SSMCH) in collaboration with National Institute of Cardiovascular Diseases (NICVD), Dhaka over a period of one year from July 2013 to June 2014. A total of 30 single-tone pregnant women of 20-40 weeks gestation with preeclampsia were taken as cases. An equal number of gestationally-matched healthy pregnant (HP) women of similar age cohorts having no history of preexisting hypertension were included as controls. Preeclampsia was defined as SBP ≥140and/or DBP ≥ 90 mmHg after 20 weeks gestation in a woman with previously normal blood pressure and with proteinuria≥1 + in the dipstick test. Pregnant women with systolic and diastolic blood pressures within the normal range (< 140mmHg and > 90 mmHg respectively), trace or absence of proteinuria by dipstick test were defined as controls. All thesubjects were investigated with ECG, standard two-dimensional, M-mode, and Doppler transthoracic echocardiography. The cardiac functional and structural changes were measured in terms of interventricular septal thickness (IVSTd),posterior wall thickness (PWTd), left ventricular internal diameter at the end of diastole (LVIDd), ejection fraction (EF), transmitral velocity (MV E/A ratio), MV deceleration time (MV DecT). Result: Half of the women with preeclampsia were primigravidae and there was no association between gravidity and the occurrence of preeclampsia. Prepregnancy overweight or obesity (in terms of BMI) was found to be strongly associated with preeclampsia. One in 10 PE women had a previous history of preeclampsia as opposed to none in the HP women. A substantial proportion (56.7%) of PE women had a family history of hypertension in comparison to healthy pregnant women (16.3%). The women with PE had significantly higher SBP, DBP, & MAP than the HP women. Parameters of diastolic dysfunction, like mitral E/A ratio was reduced and deceleration time was prolonged in PE with diastolic dysfunction (mean E/A ratio < 0.73 and mean DceT >178 ms respectively) than those in PE with normal diastolic function (mean E/A ratio 1.2 and mean DceT 192.4 ms respectively) healthy pregnant women (mean E/A ratio 1.3 and mean DecT 186.5 ms respectively). Over one-third (36.7%) of women with PE met the criteria of diastolic dysfunction compared to none in healthy pregnant women. The LVH appears to be a frequent occurrence in pregnancies complicated by preeclampsia (43.3%) as compared to none in healthy pregnant women. In the present study, the systolic function was assessed with the help of EF, which was well-preserved both in PE and HP with no significant intergroup difference. Conclusion: Preeclampsia is associated with left ventricular diastolic dysfunction and hypertrophy preserving the systolic function. These structural and functional changes are primarily adaptive in nature for maintaining cardiac systolic function. Ibrahim Card Med J 2022; 12 (2): 32-39